2005
DOI: 10.1074/jbc.m506654200
|View full text |Cite
|
Sign up to set email alerts
|

Development of Zinc Finger Domains for Recognition of the 5′-CNN-3′ Family DNA Sequences and Their Use in the Construction of Artificial Transcription Factors

Abstract: Considerable progress has been made in recent years in the design of transcription factors for the directed regulation of endogenous genes. Although many strategies involve selection methods that must be applied for each new target sequence, we have developed an approach based on linkage of predefined zinc finger domains that each recognize a three-base pair DNA sequence to construct artificial transcription factors that bind to a desired sequence. These domains can be assembled to recognize unique 18-base pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
147
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(150 citation statements)
references
References 42 publications
(112 reference statements)
1
147
0
2
Order By: Relevance
“…A BLAST-Search on the human genome has revealed that the three 18-bp targeted sites in the maspin promoter are unique (data not shown). Targets À126 and À97 were selected based on their close proximity to the transcription start site and because of the highly specific interactions predicted for the DNA triplets and the available ZF lexicons (Segal et al, 1999;Dreier et al, 2000Dreier et al, , 2002Dreier et al, , 2005. In addition to the proximal ATF sites, we have designed an ATF recognizing an 18-bp site comprising the hormone response element (HRE) sequence, which interacts with the hormone receptor both in breast (Khalkhali-Ellis et al, 2004) and prostate (Zhang et al, 1997) cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A BLAST-Search on the human genome has revealed that the three 18-bp targeted sites in the maspin promoter are unique (data not shown). Targets À126 and À97 were selected based on their close proximity to the transcription start site and because of the highly specific interactions predicted for the DNA triplets and the available ZF lexicons (Segal et al, 1999;Dreier et al, 2000Dreier et al, , 2002Dreier et al, , 2005. In addition to the proximal ATF sites, we have designed an ATF recognizing an 18-bp site comprising the hormone response element (HRE) sequence, which interacts with the hormone receptor both in breast (Khalkhali-Ellis et al, 2004) and prostate (Zhang et al, 1997) cells.…”
Section: Resultsmentioning
confidence: 99%
“…(b) a-Helical ZF sequences engineered to bind their corresponding target DNA triplets. These ZF sequences were chosen based on the available specific ZF lexicons (Segal et al, 1999;Dreier et al, 2000Dreier et al, , 2001Dreier et al, , 2005. The 6ZF ATFs were constructed by overlapping PCR; Supplementary methods).…”
Section: Resultsmentioning
confidence: 99%
“…A single zinc finger motif consists of 28 amino acids and includes an α-helix that contacts three bases in the major groove of DNA. Through modular assembly of such zinc finger modules, artificial DNA-binding domains can be created to bind to a wide 15 variety of DNA sequences [10][11][12][13][14] . A DNA-binding domain consisting of three zinc finger motifs has hence the potential to bind 9 bp of DNA.…”
Section: Introductionmentioning
confidence: 99%
“…A DNA-binding domain consisting of three zinc finger motifs has hence the potential to bind 9 bp of DNA. Many engineered 3-finger proteins have been shown to have excellent binding specificity in vitro, while others were less specific [10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] To date, ZF domains that recognized almost all of the GNN, ANN and CNN DNA triplets have been identified. [10][11][12][13][14] Approaches other than modular assembly also provide access to polydactyl ZF proteins. 15 Artificial transcription factors that use ZFs for DNA recognition typically use six ZFs to recognize 18 bases of DNA; this length of sequence is theoretically unique in the genome.…”
Section: Introductionmentioning
confidence: 99%